2022
DOI: 10.1093/cvr/cvac019
|View full text |Cite
|
Sign up to set email alerts
|

Renin, aldosterone, the aldosterone-to-renin ratio, and incident hypertension among normotensive subjects from the general population

Abstract: Aims To investigate the predictive ability of direct plasma renin and aldosterone concentrations as well as their ratio (aldosterone-to-renin (ARR)) for incident hypertension in the general population. Methods and Results Concentration of renin and aldosterone were measured by a chemiluminescence immunoassay (CLIA) using the fully-automated LIAISON® platform (DiaSorin) among 5,362 participants of the population-based Gutenber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, the Raine Study found that higher ARR at 17 years of age was associated with higher blood pressure at 27 years of age 20 . Moreover, given evidence for increased risk of incident hypertension in people with low renin and high aldosterone levels, 7,26 the relationship between ARR and blood pressure may evolve over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Raine Study found that higher ARR at 17 years of age was associated with higher blood pressure at 27 years of age 20 . Moreover, given evidence for increased risk of incident hypertension in people with low renin and high aldosterone levels, 7,26 the relationship between ARR and blood pressure may evolve over time.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of positive screening test results depends on its definition; the threshold we applied (70 pmol/mU) is typical for Australian practice, 13 and no minimum plasma aldosterone concentration was required; this relatively high threshold yields a conservative estimate of the number of participants with possible primary aldosteronism 30 . Finally, primary aldosteronism screening was not conducted according to the international Endocrine Society recommendations, 31 (ie, we screened all participants, not just those with higher blood pressure or resistant hypertension) as abnormal aldosterone regulation has been identified in some people without hypertension, 7,26,32 suggesting that its production can begin to rise prior to the onset of hypertension 6 …”
Section: Discussionmentioning
confidence: 99%
“…The potential of RAAS proteins as biomarkers predicting new-onset of HT was long limited and not consistent between studies mainly due to the analytical challenges in protein measurement methods [29]. However, a recent study revealed that aldosterone-to-renin ratio obtained by simultaneous measurement of both analytes using fully automated chemiluminescence immunoassay (CLIA), possesses a relatively stronger predictive potential for incidental HT, compared to individual aldosterone or renin levels [30]. This novel analytical method may be used in the future in large-scale biobanks allowing testing causal relationships between RAAS proteins and BP traits.…”
Section: The Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%